The Vice-Chancellor’s Message on the Occasion of Hari Raya Aidil Fitri 1437H: MADRASAH OF RAMADAN, THE BEST EDUCATIONAL INSTITUTION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
Ramadhan is likened to a 'madrasah', the best educational institution from Allah SWT. The ‘degree’ that we receive during our ‘graduation’ today is based on how well we have performed throughout.